Gendered housing matters: toward gender-responsive data and policy making - Stone, W.; Sharam, A.; Goodall, Z.; Reynolds, M.; Sinclair, S.; Faulkner, D.; James, Amity; Zhang, Thomas (2024)
With peoples’ gender having a real impact of their ability to find safe, affordable housing, new AHURI research highlights that policy makers and support services need to develop secure and accurate data collection and collation practices in order to improve outcomes. It is critically important that researchers can provide confidence to participants and end-users that gender-related data will be gathered respectfully, treated securely, stored securely and used only for legitimate evidence and policy purposes.